2018
DOI: 10.1177/0011000018777544
|View full text |Cite
|
Sign up to set email alerts
|

Survivors’ Perspectives on Recovery From Commercial Sexual Exploitation Beginning in Childhood

Abstract: This study explored the process of exiting and recovery from commercial sexual exploitation beginning in childhood, utilizing semistructured interviews with 11 adult female survivors who had been out of the commercial sex industry for at least six months. The narratives were analyzed using consensual qualitative research. Participants described a complex interface of internal motivation and external resources in the exiting process. They identified a need for comprehensive, nonjudgmental services across all st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…evaluated each article, scoring them separately using a 9-point critical appraisal assessment tool adapted from Madigan et al 40 (2018), based on previous meta-analytic research. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Articles were given a score of 0 (no) or 1 (yes) for each criterion and summed to provide a total score of a possible 9. Higher scores correspond with higher methodological quality and lower risk of bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…evaluated each article, scoring them separately using a 9-point critical appraisal assessment tool adapted from Madigan et al 40 (2018), based on previous meta-analytic research. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Articles were given a score of 0 (no) or 1 (yes) for each criterion and summed to provide a total score of a possible 9. Higher scores correspond with higher methodological quality and lower risk of bias.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, policy analysts, researchers, and professionals have advocated for multidimensional CSE prevention and intervention programs, which necessitate collaboration across health care providers, schools, and social services to support the needs of the child. 36 However, despite growing documentation of CSE factors, the present evidence base only identifies unilateral risk factors or consists of studies insufficient in quality to meaningfully guide prevention and intervention. 33 …”
Section: Introductionmentioning
confidence: 99%
“…Sexual activity before marriage for adolescents is strongly discouraged in Tanzania (McCleary-Sills et al, 2016), so they are generally reticent about disclosing any unwanted sexual experiences, such as SE (Kisanga et al, 2013). Besides, younger victims are often prevented from escaping SE by their exploiters (Bruhns et al, 2018). We proposed that younger adolescents subject to SE will be less likely to seek help than older adolescents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, self-efficacy can have opposite effects. Individuals with high levels of self-efficacy were found to be less likely to seek help from professionals if they suffered from depression, career concerns, or alcohol or drug use (Hess & Tracey, 2013), while SE survivors in a qualitative study noted that a sense of self-efficacy was essential for exiting the sex industry (Bruhns et al, 2018). In this study, we assumed that adolescents with generally higher levels of self-efficacy will have greater intentions to seek help regarding SE, and that the aforementioned TPB variables would be positively related to their intentions to seek help.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, service providers indicated that many of the trafficked youth they encounter have low self-esteem, feelings of shame or guilt, and a general sense of fear (Gerassi et al, 2018). In addition, youth also feel a sense of isolation and loneliness after being trafficked that affects many of their personal relationships and connections to their community (Bruhns et al, 2018). In order for survivors to reconcile other needs throughout their recovery, both psychological and interpersonal mental health challenges must be addressed.…”
Section: Literature Reviewmentioning
confidence: 99%